2014
DOI: 10.5539/ies.v7n4p47
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Relations among Parental Involvement, School Engagement and Academic Performance of High School Students

Abstract: The author proposed a model to explain how parental involvement and school engagement related to academic performance. Participants were (671) 9th and 10th graders students who completed two scales of "parental involvement" and "school engagement" in their regular classrooms. Results of the path analysis suggested that the parental involvement influences school engagement directly. Also, parental involvement influences academic performance indirectly through its effects on school engagement. In addition, schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 39 publications
1
27
0
1
Order By: Relevance
“…More specifically, results of this study are also consistent with the results of previous studies regarding positive role of parent or family involvement in student engagement (Mulya & Qudsyi, 2017;Al-Alwan, 2014;Murray, 2009;Malczyk & Lawson, 2017;Simons-Morton & Chen, 2009;Furrer & Skinner, 2003), the role of peers in student engagement (Sa'diyah & Qudsyi, 2016;Arifani & Qudsyi, 2018;Patrick, Ryan, & Kaplan, 2007;Bishop & Pflaum, 2005;Kizildag, Demirtas-Zorbaz, & Zorbaz, 2017;Furrer & Skinner, 2003), the role of teacher or school in student engagement (Krauss, Kornbluh, & Zeldin, 2017;Jani & Qudsyi, 2017;Martin & Rimm-Kaufman, 2015;Patrick, Ryan, & Kaplan, 2007;Murray, 2009;Furrer & Skinner, 2003), and the role of student self-efficacy in student engagement (Husnita & Qudsyi, 2017;Martin & Rimm-Kaufman, 2015;Oriol-Granado, Mendoza-Lira, Covarrubias-Apablaza, & Molina-Lopez, 2017). Thus, this study can corroborate the results of previous studies which showed a relationship between parental involvement, peer attachment, teacher support, and academic self-efficacy with student engagement.…”
Section: Resultssupporting
confidence: 92%
“…More specifically, results of this study are also consistent with the results of previous studies regarding positive role of parent or family involvement in student engagement (Mulya & Qudsyi, 2017;Al-Alwan, 2014;Murray, 2009;Malczyk & Lawson, 2017;Simons-Morton & Chen, 2009;Furrer & Skinner, 2003), the role of peers in student engagement (Sa'diyah & Qudsyi, 2016;Arifani & Qudsyi, 2018;Patrick, Ryan, & Kaplan, 2007;Bishop & Pflaum, 2005;Kizildag, Demirtas-Zorbaz, & Zorbaz, 2017;Furrer & Skinner, 2003), the role of teacher or school in student engagement (Krauss, Kornbluh, & Zeldin, 2017;Jani & Qudsyi, 2017;Martin & Rimm-Kaufman, 2015;Patrick, Ryan, & Kaplan, 2007;Murray, 2009;Furrer & Skinner, 2003), and the role of student self-efficacy in student engagement (Husnita & Qudsyi, 2017;Martin & Rimm-Kaufman, 2015;Oriol-Granado, Mendoza-Lira, Covarrubias-Apablaza, & Molina-Lopez, 2017). Thus, this study can corroborate the results of previous studies which showed a relationship between parental involvement, peer attachment, teacher support, and academic self-efficacy with student engagement.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, it was noted in a survey of over 236 Malaysian students that weak association found between the online game and student's academic performance (Eow, Ali, Mahmud, & Baki, 2009). In a survey of 671 students in Jordan, it was revealed that student's engagement directly influences academic performance, also seen the indirect effect of parental involvement over academic performance (Al-Alwan, 2014). Engaged students are perceptive and highly active in classroom activities, ready to participate in different classroom extra activities and expose motivation to learn, which finally leads in academic achievement (Reyes, Brackett, Rivers, White, & Salovey, 2012).…”
Section: Research Background and Hypothesesmentioning
confidence: 99%
“…Literature has shown that parental involvement in child development is a strong predictor of a positive educational trajectory (Barlow and Humphrey, 2012; Al-Alwan, 2014). The style of parental involvement can be a promoter of more, or less, autonomy and participation of children in their activities (Raftery et al, 2012).…”
Section: Introductionmentioning
confidence: 99%